A modeling study of the effect of runoff variability on the effective pressure beneath Russell Glacier, West Greenland. Issue 10 (15th October 2016) - de Fleurian, Basile; Morlighem, Mathieu; Seroussi, Helene; Rignot, Eric; van den Broeke, Michiel R.; Kuipers Munneke, Peter; Mouginot, Jeremie; Smeets, Paul C. J. P.; Tedstone, Andrew J.
Abstract: Basal sliding is a main control on glacier flow primarily driven by water pressure at the glacier base. The ongoing increase in surface melting of the Greenland Ice Sheet warrants an examination of its impact on basal water pressure and in turn on basal sliding. Here we examine the case of Russell Glacier, in West Greenland, where an extensive set of observations has been collected. These observations suggest that the recent increase in melt has had an equivocal impact on the annual velocity, with stable flow on the lower part of the drainage basin but accelerated flow above the Equilibrium Line Altitude (ELA). These distinct behaviors have been attributed to different evolutions of the subglacial draining system during and after the melt season. Here we use a high‐resolution subglacial hydrological model forced by reconstructed surface runoff for the period 2008 to 2012 to investigate the cause of these distinct behaviors. We find that the increase in meltwater production at low elevation yields a more efficient drainage system compatible with the observed stagnation of the mean annual flow below the ELA. At higher elevation, the model indicates that the drainage system is mostly inefficient and is therefore strongly sensitive to an increase in meltwater availability, which is consistent with the observed increase in ice velocity. Key Points: A subglacial hydrology model produces a multiyear simulation of water pressure coherent with observed surface uplift The model results confirm the existence of two distinct modes of behavior of the subglacial water pressure in Russell region